An Improved Gravitational Search Algorithm For Optimal Placement And Sizing Of Renewable Distributed Generation Units In A Distribution System For Power Quality Enhancement - Abdul Kadir, Aida Fazliana; Mohamed, Azah; Shareef, Hussain; Ibrahim, Ahmad Asrul (AIP Publishing, 2014)
-